Adolescent Mental Health 2015
DOI: 10.1201/b18222-7
|View full text |Cite
|
Sign up to set email alerts
|

- Adolescent Health-Risk Behavior and Community Disorder

Abstract: Students negotiate the transition to secondary school in different ways. While some thrive on the opportunity, others are challenged. A prospective longitudinal design was used to determine the contribution of personal background and school contextual factors on academic competence (AC) and mental health functioning (MHF) of 266 students, 6-months before and after the transition to secondary school. Data from 197 typically developing students and 69 students with a disability were analysed using hierarchical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Additional support needs (e.g., due to disability, English as additional language, socio‐economic disadvantage) have been seen to be risk factors during primary‒secondary transitions. Only five studies compared typically developing pupils with peers who had an additional support need (Bloyce & Frederickson, ; Vaz, Falkmer, Parsons, et al , ; Vaz, Parsons, Falkmer, et al , ; Foley et al , ; Neal et al , ). Vaz, Falkmer, Parsons, et al () reported that social disadvantage had a detrimental effect on academic competence and mental health functioning and argued that pupils from these backgrounds therefore need a higher level of support than their peers.…”
Section: Resultsmentioning
confidence: 99%
“…Additional support needs (e.g., due to disability, English as additional language, socio‐economic disadvantage) have been seen to be risk factors during primary‒secondary transitions. Only five studies compared typically developing pupils with peers who had an additional support need (Bloyce & Frederickson, ; Vaz, Falkmer, Parsons, et al , ; Vaz, Parsons, Falkmer, et al , ; Foley et al , ; Neal et al , ). Vaz, Falkmer, Parsons, et al () reported that social disadvantage had a detrimental effect on academic competence and mental health functioning and argued that pupils from these backgrounds therefore need a higher level of support than their peers.…”
Section: Resultsmentioning
confidence: 99%
“…Personal factors, such as socio-economic status (SES) and gender, particularly seem to be predictive factors for the perceived threat from the transition to secondary school (Sirsch, 2003). A lower SES may lead to lower achievement (Vaz, Parsons, Falkmer, Passmore & Falkmer, 2014). Among children from low socio-economic households, 72% did not get used to the routines at secondary school and 58% did not settle in very well (Evangelou et al, 2008).…”
Section: Child and Family Characteristicsmentioning
confidence: 99%
“…Children are at risk of not expanding their friendships and boosting their self-esteem and confidence if they experience bullying while in secondary school. Problems with bullying are most acute among children with special education needs (SEN) (Vaz et al, 2014). Of those, 37% have problems with bullying, compared with 25% of the children without SEN (Evangelou et al, 2008).…”
Section: Child and Family Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations